Involvement of the superoxide dismutase enzyme in the mycorrhization process - Justo Arines; Antonio Vilariňo; José M. Palma (Agricultural and Food Science, 1994)
The survivability and quality of micropropagated plants can be improved through mycorrhization. We consider that mycorrhization is important in supporting plants under stress conditions. The mechanism is not fully understood, but it seems that the enzymes involved in alleviating stress are important factors. We therefore studied superoxide dismutase (SOD; EC 1.15.1.1) isozymes. Insight is provided into the generation of superoxide radicals (SORs) and the detoxification role of SOD isozymes. Examples of how the expression of this enzyme changes in symbiotic processes are also given.